The handmaid's tale. Season five [videorecording (DVD)] - Moss, Elisabeth, 1982-; Strahovski, Yvonne, 1982-; Fiennes, Joseph, 1970-; Dowd, Ann; Atwood, Margaret, 1939- (MGM, 2023)
In Season Five of the Handmaid's Tale, June faces consequences for killing Commander Waterford while struggling to redefine her identity and purpose. The widowed Serena attempts to raise her profile in Toronto as Gilead's influence creeps into Canada. Commander Lawrence works with Nick and Aunt Lydia as he tries to reform Gilead and rise to power. June, Lucke, and Moira fight Gilead from a distance as they continue their mission to save and reunite with Hannah.